Influence of seed moisture and storage conditions on seed quality parameters in bael (Indian Journal of Arid Horticulture, 2025)
Viable seeds of bael (Aegle marmelos L.) are essentially required for raising rootstocks and propagation. The effect of seed moisture at various levels and their relationship with some physiological parameters was studied in bael. The overall result depicted conversely, less moisture contents (2 and 5%) in seeds influenced more germination percentage and vigour index under all conditions of storage that high moisture (10%) level in seeds which have been stored for three years at all storage temperatures have significantly influenced least survival rates. The electrical conductance and UV-absorbance were low with less moisture level in seeds. The importance of seed moisture and storage conditions is discussed in the paper.
Keywords: Bael; seed germination; vigour index; storage conditions